Pembekalan Manajemen Kesehatan Pasien COVID 19 di Pusat Isolasi Mandiri Bagi Volunteer Keperawatan - Suci Tuty Putri; Septian Andriyani; Tirta Adikusuma; Sri Sumartini; Sehabudin Salasa (LPPM UNINUS, 2022)
The development of the COVID-19 pandemic is still increasing in the community. With the large population in Indonesia, especially the city of Bandung, the treatment of COVID-19 patients is not only carried out at health service centers but also in the community directly. Health volunteers who are community groups who are actively assisting the government in the implementation of public health need to be equipped with the management of COVID-19 patient care in terms of care, nutrition and exercise. This PKM aims to provide debriefing to prospective COVID volunteers regarding the care of individuals with COVID 19 in hospitals and self-isolation places in the community, sports training in handling COVID, debriefing knowledge and skills in the implementation of infection prevention and control in treating COVID patients. The method used is blended seminars and training, namely online and offline by implementing strict health protocols. This program is carried out for 2 days. Participants are 244 students, health workers who are prospective COVID 19 volunteers at health institutions in the city of Bandung. The results of the activity showed that there was an increase in the average knowledge of pretest (65.8), post test (73.49) of volunteers on nursing care management, and skills in safety preparation.